2012
DOI: 10.1073/pnas.1121081109
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam suppresses neuronal network dysfunction and reverses synaptic and cognitive deficits in an Alzheimer’s disease model

Abstract: In light of the rising prevalence of Alzheimer's disease (AD), new strategies to prevent, halt, and reverse this condition are needed urgently. Perturbations of brain network activity are observed in AD patients and in conditions that increase the risk of developing AD, suggesting that aberrant network activity might contribute to AD-related cognitive decline. Human amyloid precursor protein (hAPP) transgenic mice simulate key aspects of AD, including pathologically elevated levels of amyloid-β peptides in bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
559
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 566 publications
(615 citation statements)
references
References 70 publications
(80 reference statements)
51
559
3
2
Order By: Relevance
“…A recent clinical study of AD patients has revealed that convulsive seizures occurred early in the course of AD, which often began around the same time when symptoms of neurodegeneration first appeared (55). Levetiracetam, which inhibits presynaptic calcium channels (56), suppresses neuronal hyperactivation, and reverses cognitive deficits in their AD model mice (57). These results are consistent with our findings (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…A recent clinical study of AD patients has revealed that convulsive seizures occurred early in the course of AD, which often began around the same time when symptoms of neurodegeneration first appeared (55). Levetiracetam, which inhibits presynaptic calcium channels (56), suppresses neuronal hyperactivation, and reverses cognitive deficits in their AD model mice (57). These results are consistent with our findings (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with the effects of hTau‐A152T and hTau‐WT on evoked and spontaneous epileptic activity, expression of either hTau species enhanced the increased risk of early death in hAPP mice, which have epileptiform activity even in the absence of hTau overexpression 46, 49. hTau‐A152T was more detrimental in this regard than hTau‐WT.…”
Section: Discussionsupporting
confidence: 56%
“…The two diseases also exhibit significant comorbidity 51 . An antiepileptic drug (levetiracetam) was recently found to reverse deficits in learning and memory in AD mice and might also help ameliorate related abnormalities in human 52 . Symptoms represent the high-level manifestations of a disease that are actually observed by patients and physicians.…”
Section: Discussionmentioning
confidence: 99%